RECONTEXTUALIZING THE WORDS “DISTANCE” AND “DISTANCING” DURING THE COVID-19 PANDEMIC - Lidinillah, Moh Kavin; Zuhri, Moh Shofi (Al Qolam University, 2024)
COVID-19 is a plague that has become a pandemic for the world. Necessary, many researchers who conduct research to understand about COVID-19, both medical and other scientific disciplines such as language science. The purpose of this study is to find out whether there is a contextualization of the words DISTANCE and DISTANCING with SOCIAL kolokat. For this reason, the mixed method is used to obtain coherent results. The results of this study indicate that the T-score of DISTANCING 16.1 and DISTANCE -14. This shows that the word SOCIAL is more commonly used with the word DISTANCING in corpora. The second finding is a re-contextualization of the word DISTANCING in the negative direction. Keywords: Corpus-Based Analysis, Critical Strategies, COVID-19, Recontextualization